Hubungan antara Penerimaan Diri dengan Kecemasan pada Wanita Menopause - Dyah Mustikaningtyas Dewanti; Yoseph Indrayanto; Ruben Dharmawan (Nexus Kedokteran Komunitas, 2013)
Background: Anxiety of menopausal women may appear because they have to adjust to the aging process. Anxiety will become pressure and burden if she always thinks negatively. Self-acceptance is the ability of individuals to accept themselves which is characterized by self-confidence and self-appreciation. Self-acceptance can reduce the possibility of a person to think of anything that can stimulate anxiety. This study aims to determine the relation between self-acceptance and anxiety of menopausal women. Method: This research was observational analytic study with cross-sectional approach by using purposive random sampling technique. This research was conducted from March to April 2013 at Posyandu Dahlia RW XIX Nusukan, Posyandu RW XIV Nusukan and Posyandu Pucang Sawit. The number of sample was 35 menopausal women who were appropriate to the inclusion criteria. The sampling of this research are the women who had menopause for 1-2 years, women with unpathological menopause, L-MMPI scores with NO answers <10, and the women who are able to be the respondents to fill in and accept the informed consent. The subject of the research filled (1) informed consent (2) curriculum vitae form (3) L-MMPI questionnaire to evaluate the respondents truthfulness in answering questionnaire (4) Bergers Self-Acceptance Scale questionnaire to find out the self-acceptance score (5) Taylor Manifest Anxiety Scale questionnaire to find out the anxiety score. Data were analyzed using Pearson Product Moment correlation test through SPSS 17.00 for Windows. Result: Based on the data analysis, p = 0.0001 (p < 0.05) and Pearson correlation value (r) = -0.627. Conclusion: There is a strong negative correlation between self-acceptance and anxiety of menopausal women. Keywords: self-acceptance, anxiety, menopausal women